2021
DOI: 10.3390/molecules26092565
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Antioxidant Enhancing Properties of Selective Equisetum Extracts

Abstract: The sterile stems belonging to the Equisetum species are often used in traditional medicine of various nations, including Romanians. They are highly efficient in treating urinary tract infections, cardiovascular diseases, respiratory tract infections, and medical skin conditions due to their content of polyphenolic derivatives that have been isolated. In this regard, this study aimed to provide the chemical composition of the extracts obtained from the Equisetum species (E. pratense, E. sylvaticum, E. telmatei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…The lowest scavenging activity of the hydroxyl radical was recorded for Ep–AgNPs. The same order was observed in the case of extracts, as well [ 53 ]. In Figure 8 , it can be seen that at a concentration of 0.625 mg/mL, the used standard (gallic acid), Ep–AgNPs and Et–AgNPs show approximately the same scavenging capacity.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The lowest scavenging activity of the hydroxyl radical was recorded for Ep–AgNPs. The same order was observed in the case of extracts, as well [ 53 ]. In Figure 8 , it can be seen that at a concentration of 0.625 mg/mL, the used standard (gallic acid), Ep–AgNPs and Et–AgNPs show approximately the same scavenging capacity.…”
Section: Resultssupporting
confidence: 74%
“…Among the obtained nanoparticles, the lowest efficiency regarding LOX inhibition can be seen for Et–AgNPs. The constituents of E. sylvaticum seem to possess the most important capacity of inhibiting LOX, taking into account results from previous studies [ 53 ] and the fact that only Es–AgNPs showed a higher efficiency compared to gallic acid.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…To further evaluate the safety of WBS, we performed an experimental analysis of the behavior of adult fish. Behavioral testing was performed using the novel tank test (NTT), which was used to assess the anxiety-like response [ 26 ]. Briefly, the NTT was a trapezoidal tank (1.5 L, 15 height × 28 top/22 bottom × 7 width cm) that was essentially divided into top and lower halves [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition of the enzyme was evaluated using a modified Malterud method [70,91]. 50 µL Glycine max lipoxidase in borate buffer was treated with 50 µL of a sample/control solution of varying concentrations in DMSO and allowed to stand for 10 min.…”
Section: Lipoxygenase Inhibitionmentioning
confidence: 99%